2020
DOI: 10.1007/s10683-020-09646-y
|View full text |Cite
|
Sign up to set email alerts
|

Would depositors pay to show that they do not withdraw? Theory and experiment

Abstract: In a Diamond-Dybvig type model of financial intermediation, we allow depositors to announce at a positive cost to subsequent depositors that they keep their funds deposited in the bank. Theoretically, the mere availability of public announcements (and not its use) ensures that no bank run is the unique equilibrium outcome. Multiple equilibria-including bank run-exist without such public announcements. We test the theoretical results in the lab and find a widespread use of announcements, which we interpret as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Experimental evidence also shows that deposit insurance diminishes the incidence of bank runs, albeit it does not eliminate them completely (Schotter and Yorulmazer, 2009;Kiss et al, 2012;Peia and Vranceanu, 2019). 1 Our study is also related to Kinateder et al (2020), who assume that only withdrawals are observed as a default, but depositors can make visible to subsequent depositors the decision to keep their funds deposited (at a modest cost). In this environment, the iterated elimination of dominated strategies implies that the mere possibility of the costly announcement should be enough to eliminate bank runs.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Experimental evidence also shows that deposit insurance diminishes the incidence of bank runs, albeit it does not eliminate them completely (Schotter and Yorulmazer, 2009;Kiss et al, 2012;Peia and Vranceanu, 2019). 1 Our study is also related to Kinateder et al (2020), who assume that only withdrawals are observed as a default, but depositors can make visible to subsequent depositors the decision to keep their funds deposited (at a modest cost). In this environment, the iterated elimination of dominated strategies implies that the mere possibility of the costly announcement should be enough to eliminate bank runs.…”
Section: Introductionmentioning
confidence: 70%
“…24 This finding is in line with previous evidence on bank runs. For example, Kinateder et al (2020) test experimentally a different mechanism to prevent bank runs, also based on the principle of iterated elimination of dominated strategies. They also find that participants frequently use the action introduced to dominate withdrawal instead of opting to keep the money in the bank.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation